Anti diabetic effect of CL 316,243 (a β3-adrenergic agonist) by down regulation of tumour necrosis factor (TNF-α) expression. - Masoud Ghorbani; Mehdi Shafiee Ardestani; Sedigheh Hatami Gigloo; Reza Ahangari Cohan; Davoud Nouri Inanlou; Peyman Ghorbani (PLoS ONE, 2012)
OBJECTIVE: Obesity is a risk factor for the development of insulin resistance and is one of the most important contributors to the pathogenesis of type 2 diabetes, which acts mainly through the secretion of adipokines such as TNF-α that may influence insulin sensitivity. TNF-α affects many aspects of adipocyte function, such as adipocyte development and lipid metabolism. MATERIAL AND METHODS: We demonstrated that there is a correlation between the expressions of TNF-α in retroperitoneal WAT and insulin-resistance in 8 genetically obese fa/fa rats. Treatment of animals with CL 316,243, a β3-adrenergic agonist, showed an improvement of insulin-resistance that was linked with the suppression of TNF-α mRNA expression in WAT. RESULTS: These results confirm the association between TNF-α expression and the insulin-resistant condition in rats. Our finding indicates that the hyperglycaemia and hyperinsulinemia induced by insulin-resistance correlated positively with the expression of TNF-α mRNA in an abdominal WAT depot. CONCLUSION: We conclude that CL 316,243 possesses both anti-diabetic effects and anti-obesity effects in rodents.